The impact of financial development on corporate finance of emerging market / Nur Khairina Aida Kamaruddin - Kamaruddin, Nur Khairina Aida (Faculty of Business Management, 2017)
This paper is to study the effects of financial development on corporate financing of emerging market firms to ascertain whether have relationship or any impact in the financial market on the available choice of financing of firms. The dependent variable for this study is Capital Structure which is measure by Debt to GDP. The independent variables is Bank Credit deﬁned as the ratio of bank assets to gross domestic product (GDP) divided by the ratio of market capitalization to GDP; Private Credit is domestic credit to the private sector as a percentage of GDP; Stock Market Development is stock market capitalization to GDP; Profitability is using return on equity; and M3 deﬁned as ratio of liquid liabilities to GDP. Panel data were used to run the regression in this study. The sample under the study consists of 17 emerging market which measure for 9 years from 2006 to 2014 and used secondary data for this study. Data are collected from The World Bank website. This study will use the E-view 8 software to test and analyze the data that had been collected. The analysis that will be use to analyze the data is Descriptive analysis, Stationary test, Normality test, Correlation analysis and Regression analysis. Also use Test on assumption to test the data.